Inovação social: rumo a uma mudança experimental na política pública? - Lars Hulgård; Adriane Vieira Ferrarini (Ciências Sociais Unisinos)
Since the early 1990s, the process of privatization and marketization of public policy led to the individualization and fragmentation of programs, but it also gave the opportunity for strengthening the structure of civil society and the expansion of its capacity to intervene in social reality. Social innovation and social entrepreneurship arise as important factors for the renewal of the welfare state. The change in social structure was studied by the EMES-European Research Network from the perspective of the emergence of a new type of social entrepreneurship and social enterprise. There are studies that define social innovation and social entrepreneurship as distinct concepts, but in this article we will define them almost as synonymous in that they both combine the creation of socialvalue with change and consider the need for integration between process and outcome. In the light of this theoretical approach, social entrepreneurship and social innovation in public policy are closely related to the participatory and democratic structures of government and emerge at the intersection of state, market and civil society. The Nordic countries show a trend of active support from the state to civil society but in Brazil theemergence of social entrepreneurial principles starting from the end of the 1980s, with the universalization and democratization of public policy. That led to a significant number of trials of new participatory and integrated institutional arrangements from the principles of decentralization, social control and participation of civil society, which can be regarded as a process of social innovation.